ASEAN open skies : economic integration and SAR - Tsjeng, Henrick Zhihao (2014)
The ASEAN Open Skies agreement promises to bring greater economic integration. However, this will require enhancements in aviation facilities and fleets, and, as MH370 has demonstrate, a strengthening in search-and-rescue cooperation.